If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + 6x + -6 = 23 Reorder the terms: -1 + -6 + 6x = 23 Combine like terms: -1 + -6 = -7 -7 + 6x = 23 Solving -7 + 6x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 6x = 23 + 7 Combine like terms: -7 + 7 = 0 0 + 6x = 23 + 7 6x = 23 + 7 Combine like terms: 23 + 7 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| 3y-5x=x+9 | | 5x-2/3-6 | | x^2+14-7=0 | | 6n+n=2860 | | 0.2x+5.7+4.9=10.2266 | | 4a+r= | | 26x-24=56 | | v^2=2 | | g-78=876 | | 6c-8-2c=-7 | | 0.17x-0.4(x+1700)=-2556 | | 20/0= | | 2t+2.2H=-3.7 | | X-108=36 | | x+3y-3z=-26 | | 2(6x+8)-2(3x-6)= | | 3x-8=-2(4x-2) | | H-3.5=5 | | 9(-5/8) | | 23.42-x=15.42 | | 4.12-c=2.45 | | -8x-14y=52 | | 4x+34+6x-14=180 | | 1-3/2x=5/6 | | 7x-(2x+5)=3x+7 | | -6+7x-4x=15 | | 78=6x+6 | | x+11.5=20.5 | | -16=.8a | | 3/4÷3/2 | | 3(k+1)+2=17 | | 7/9x=6/2/9 |